Mechanical traumatic injuries as a cause of death in free-ranging neotropical non-human primates living in anthropogenic matrices - Rafaela Magalhães Barros; Isabel Luana de Macêdo; Davi Emanuel Ribeiro de Sousa; Yasmin Nunes Godoy da Fonseca; Liz de Albuquerque Cerqueira; Gabriela Rodrigues de Toledo Costa; Liria Queiroz Luz Hirano; Márcio Botelho de Castro (Primates, 2026)
Traumatic injuries are a major cause of morbidity and mortality in free-ranging non-human primates (NHPs), often associated with anthropogenic pressures such as habitat loss, urbanization, and interactions with domestic animals. This study characterized some epidemiological, spatial, and pathological patterns of mechanical traumatic injuries in free-ranging non-human primates from anthropogenically altered areas of the Federal District. Of 696 necropsies performed, 215 cases (30.9%) involved mechanical trauma. Black-tufted marmosets ( Callithrix penicillata ) were the most affected species (90.2%), followed by capuchins ( Sapajus libidinosus , 6.5%) and howler monkeys ( Alouatta caraya , 3.3%). Adults were more frequently affected than juveniles, with no sex-related differences. Blunt trauma accounted for the majority of cases (82.3%), most commonly as polytrauma, with cranial involvement in 65.2% of animals. Carnivore predation was the leading cause of blunt-penetrating trauma (89.4%), while gunshot injuries were rare. Bone fractures were identified in 65.1% of cases, most often involving the skull and long bones, and internal injuries were frequent in the thoracic and abdominal cavities. These findings demonstrate that mechanical trauma represents a critical threat to NHPs in urban and peri-urban areas, where exposure to human infrastructure and domestic animals is heightened. The results underscore the need for mitigation strategies to reduce mortality and support the conservation of free-ranging primate populations in human-dominated landscapes.